Hukukun yapıbozumu ve yapıbozumsal adalet - Sağlam, Rabia (My University, 2012)
Yapıbozum, mantıksal ve bilimsel bir içerikle sunulan, hakikatin ve adaletin anlamını belirleyici yegâne otorite olarak ilan edilen Batı onto-metafizik metinlerini, yapılarını ya da bütünlüklerini okuma stratejisidir. Hukuku yapıbozuma tâbi tutmaya giriştiğimizde, ötekilere bir kapı açmaya çalışan, fakat aynı zamanda hem mistik hem yasal şiddeti temsil eden ya da gerçekleştiren bir adaleti yapıbozum stratejisinin önkoşulu olarak varsaymamız gerekir. Yapıbozumsal adalet, hukuksal yapı tarafından dışlanan ya da unutulmaya terk edilen ötekiler için bir sorumluluk imkânı ve deneyimidir. Ne var ki bu adalet, ne ben ve öteki arasındaki geleneksel eşitlik algısını kapsar ne de ötekilerin farklılığını aynıya indirgeyerek verilen bir karardır. Yapıbozumsal adalet bizi, yasanın meşruiyetini sürdürebilmek için daima pratiklerinde ve söylemlerinde ima ettiği adaletin çok farklı bir boyutuna yönlendirir.

Deconstruction is a reading strategy to the Western onto-metaphysical of texts, structures or entities that presented within the logical or scientific context, and which is declared as the only determinative authority of the meaning of truth or justice. As we attempt to deconstruct to the law, we should have to assume as a precondition of deconstructive strategy that justice is an infinite and aporetic idea trying to make a room for the others, but at same time represent or pratice both mystic and legal violence. Deconstructive justice is the experience and possibility of responsibility for the others who are excluded or doomed to be forgotten by the structure of law. But this justice neither does include the mainstreams perception of equality between self and others, nor is a decision which made by reducing the difference of others to the same. Deconstructive justice leads us to a radically different aspect of justice which the law always implies it in its practices or discourses to be able to operate its legitamacy.
Keywords: Hukuk; Kamu Hukuku